Perencanaan Keuangan Bagi Pekerja Migran Indonesia di Sektor Informal - Ezar J.P.H, Egha; Prasojo, Prasojo; Pangestuti, Dinik Fitri Rahajeng (Journal of Islamic Economy and Community Engagement, 2025)
There are not a few Indonesian migrant workers in Malaysia. Many of them are workers in the informal sector. As migrant workers, sometimes they have to be able to manage their finances in order to survive there, for their families in Indonesia, and save for the future. The community service program carried out by the lecturers of the FEBI UIN Suka Sharia Accounting study program regarding financial planning is very helpful for migrant workers in Malaysia, especially workers in the informal sector. Not a few of them are interested in starting to plan their finances, starting from daily expenses to investing in the future.